Strategic Analysis of e-Business and Marketing and Sales Strategies in MSMEs - Wahyudin, Wahyudin; Hapsari, Rahma Indhytsania; Wulandari, Apriliana Ayu; Fadillah, indah Nur; Redjeki, Finny (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Electronic business (e-business) is a business activity that utilizes information technology approaches. With e-business, companies can understand all processes and developments within the organization. Additionally, business owners can make decisions based on the studies and analyses of the company's e-business. This research conducts a strategic analysis of e-business for the home industry of UMKM Wajit Pusaka Utama. The study employs SWOT analysis, Porter’s five forces model, Value chain, and critical success factors (CSF). The results of this research identify several recommended information systems for UMKM Wajit Pusaka Utama, with the hope of enhancing e-business strategies for marketing and sales processes. These information systems include a CRM (Customer Relationship Management) based Sales Information System, Financial Management Information System, Human Resource Information System, Warehouse Management System, and Geographic Information System (GIS).